Monomorphic post-transplant lymphoproliferative disorder of the tongue: case report and review of literature - Zimrin Ann; Gocke Christopher D; Burke Allen P; Tavora Fabio; Gonzalez-Cuyar Luis F; Sauk John J; Zhao Xiafeng F (BMC, 2007)
Abstract Background Post-transplant lymphoproliferative disorder (PTLD) is a spectrum of hematological diseases arising in context of immunosuppression after organ transplantation. PTLD can involve any organ; however, it is extremely rare in oral cavity. Methods Using morphologic and immunophenotypic approaches we have studied a case of monomorphic PTLD of the tongue that developed in a patient following unilateral kidney and pancreas transplantation on immunosuppressive therapy. Additionally, cases of PTLD in the oral cavity were reviewed in the English literature. Results The neoplasm showed large cell morphology and B-cell phenotype. In situ hybridization for Epstein-Barr virus was positive. Complete remission was obtained after decreasing immunosuppressive therapy. The patient remained in remission at 790 days' follow up. Conclusion This rare case increased our awareness of PTLD in the oral cavity of patients following solid organ transplantation and immunosuppressive therapy.